1966
DOI: 10.1071/bi9660831
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Concentration of Lipids and Some Other Constituents in the Blood Plasma of Calves from Birth to 6 Months of Age

Abstract: SummaryThis paper describes the changes in concentration of the major lipid fractions, glucose, and protein in plasma from the jugular vein of six calves from birth to 6 months of age. Changes in haematocrit over this period are also presented. Two-to threefold increases were observed in the plasma concentration of total fat, phospholipids, free cholesterol, and cholesterol esters within the first week after birth, with a further increase until 1 month of age. The concentration of these lipids remained high be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1
2

Year Published

1968
1968
1987
1987

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 10 publications
0
5
1
2
Order By: Relevance
“…The total cholesterol levels reported here (Table 3) for lO-month-old calves appeared to be low compared to the values obtained by other workers for calves on adequate diets (Shope 1928;Lennon and Mixner 1957;Shannon and Lascelles 1966). After the development of a fully functional rumen the plasma lipid levels appear to be independent of diet and presumably mainly influenced by normal growth processes and sex differences.…”
Section: (C) Age and Sexcontrasting
confidence: 38%
“…The total cholesterol levels reported here (Table 3) for lO-month-old calves appeared to be low compared to the values obtained by other workers for calves on adequate diets (Shope 1928;Lennon and Mixner 1957;Shannon and Lascelles 1966). After the development of a fully functional rumen the plasma lipid levels appear to be independent of diet and presumably mainly influenced by normal growth processes and sex differences.…”
Section: (C) Age and Sexcontrasting
confidence: 38%
“…Shannon & Lascelles, 1966) and it has been suggested that this is, at least in part, a reaction to cold stress (Hull, 1969). During exposure to a cold environment the levels of VLDL in rat serum drop precipitously and it is considered that this indicates an important role for this lipoprotein as a readily available energy source (Radomski, 1966).…”
Section: Fatty-acid Analysismentioning
confidence: 99%
“…Faible à la naissance, la lipémie augmente fortement au cours des premiers jours de la vie chez le Veau préruminant (Shannon et Lascelles, 1966 ;Noble etal., 1975) comme chez l'Agneau préruminant (Noble etal., 1971 (Stewart etal., 1978 ; Aurousseau, 1980 ; (Bazin et Brisson, 1976 ; Aurousseau, 1981). Les cinétiques peuvent être modifiées par la nature (Bauchart et Aurousseau, 1980) ou le taux de lipides ingérés (Bazin et Brisson, 1976), ainsi que par la nature des protéines ingérées (Toullec et al, 1979 (Thivend, 1982a) et améliore la croissance, l'efficacité alimentaire et l'état sanitaire des veaux recevant un régime riche en lipides (Thivend, 1982b Matzkies, 1975), précurseur privilégié des stérols au niveau notamment de la peau et du cerveau (Edmond, 19741. L'évolution avec l'âge de l'estercholestérolémie moyenne marquée, chez le Veau préruminant comme chez l'Agneau préruminant (Leat, 1967 ;Leat et al, 1976), par un maximum à l'âge de 3 semaines et une baisse progressive pendant les 7 semaines suivantes pourrait être directement influencée par le plan d'alimentation.…”
Section: Introductionunclassified